Hereditary galactokinase deficiency. Issue 248 (August 1971) - Cook, J. G. H.; Don, N. A.; Mann, Trevor P.
Abstract : A baby with galactokinase deficiency, a recessive inborn error of galactose metabolism, is described. The case is exceptional in that there was no evidence of gypsy blood in the family concerned. The investigation of neonatal hyperbilirubinaemia led to the discovery of galactosuria. As noted by others, the paucity of presenting features makes early diagnosis difficult, and detection by biochemical screening seems desirable. Cataract formation, of early onset, appears to be the only severe persisting complication and may be due to the biosynthesis and accumulation of galactitol in the lens. Ophthalmic surgeons need to be aware of this enzyme defect, because with early diagnosis and dietary treatment these lens changes should be reversible.